Handbook on the economics of copyright a guide for students and teachers - aWatt, Richard 1963- (Cheltenham, UK Edward Elgar Publishing, 2014)
This handbook provides comprehensive coverage of the economics of copyright, and provides a useful teaching and learning resource. The chapters deal with the basic underlying principles, the main contributing literature and, in some cases, new extensions to the field. -- Source other than the Library of Congress.
Basic economic theory of copyright / Richard Watt -- What limits indirect appropriability? / Michael Waldman -- Idea/expression dichotomy : friend or foe? / Eleonora Rosati -- Fair use doctrine: markets, market failure and rights of use / Wendy J. Gordon -- Public domain / Paul J. Heald -- Licensing of copyright works in a bargaining model / Richard Watt -- Fair remuneration for copyright holders and the Shapley value / Richard Watt -- Economics of performers' rights / Ruth Towse -- Licensing of online music streaming services in Europe / Sebastian Felix Schwemer -- Copyright collectives : some basic economic theory / Richard Watt -- Collective administration / Christian Handke -- Copying and the pricing of information goods / Richard Watt -- Impacts of internet piracy / Stan J. Liebowitz -- Law and economics of copyright remedies / Stephen E. Margolis -- Effectiveness of government anti-piracy enforcement policy : commitment versus non-commitment / Dyuti S. Banerjee -- Copyright and parallel trade / Frank Mueller-Langer -- Open source and open access: new paradigms in the theory of copyright / Richard Watt -- Copyright in visual art markets: some economic theory concerning resale royalties and other options / Richard Watt. Open source and open access: new paradigms in the theory of copyright / Richard Watt -- Copyright in visual art markets: some economic theory concerning resale royalties and other options / Richard Watt.
Includes bibliographical references and index.
Keywords: Copyright -- Economic aspects